Peran Gereja dalam Membangun Identitas Rohani Generasi Pemuda di Era Digital (Jurnal Pendidikan Agama dan Teologi, 2025)
Youth are a generation that lives in the digital era and they are very adept at using digital devices and are always updated with current technological developments. Technological developments cannot be avoided by anyone, including the church. There needs to be innovation and strategies for using technology in church services. The use of technology will make it easier for the church to reach and build the identity of youth, but on the other hand, if the church is resistant to technological developments, it is likely that church youth will withdraw and find it difficult to get involved in church activities. The role of the church in shaping the spiritual identity of the younger generation in the digital era is becoming increasingly important along with developments in technology and information. In an era where access to a variety of content and outside influences is very easy, the church has a great responsibility to ensure that young people have a solid spiritual foundation. The church can play an effective role in shaping the spiritual identity of the younger generation amidst the flow of digital information. And churches can use various methods and strategies to help youth build their spiritual identity. This includes the use of technology to spread religious teachings, the creation of supportive online communities, and the provision of targeted spiritual formation. Apart from that, the church also needs to understand the unique dynamics and challenges in the digital era, such as changes in lifestyle and values ​​faced by today's young generation.